Comparative analysis of improved m6A sequencing based on antibody optimization for low-input samples - Jiafeng Lu; Wenjuan Xia; Jincheng Li; Liya Zhang; Chunfeng Qian; Hong Li; Boxian Huang (Scientific Reports)
Abstract The most effective method for mapping N6-methyladenosine (m6A) is m6A RNA immunoprecipitation sequencing (MeRIP-seq). The quality of MeRIP-seq relies on various factors, with the anti-m6A antibody being a crucial determinant. However, comprehensive research on anti-m6A antibody selection and optimal concentrations for different tissues has been limited. In this study, we optimized the concentration of five different anti-m6A antibodies across various tissues. Our findings demonstrated that 5 µg of Millipore antibodies (ABE572 and MABE1006) performed well, starting from 15 µg total RNA from the liver, while 1.25 µg of Cell Signaling Technology antibodies (CST) (#56593) was suitable for low-input total RNA. In summary, we provide a significant guideline for anti-m6A antibody selection in MeRIP sequencing for different tissues, especially in the context of low-input RNA.